ปัจจัยที่มีความสัมพันธ์กับระยะเวลาในการตรวจสอบงบการเงินของบริษัทที่จดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - นงลักษณ์ ทองประดับเพชร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The objective of this thesis is to identify the factors influencing the amount of time of corporate financial reporting examination of the listed companies in the stock exchange of Thailand. These factors are classified into two groups: the corporate related factors and the auditor controlled factors. The study also examines the relationships between these two groups of factors and the amount of time of corporate financial reporting examination during the period before (1996-1998) and after (1999-2002) the establishment of an audit committee. The sample data are drawn from the financial reports of all companies listed in the stock Exchange of Thailand เท 1996 - 2002, excluding all the firms เท financial institution sectors (banks, finance and securities, and insurance), the firms audited by the Office of the Auditor General of Thailand and company under rehabilitation. With an average of 300 companies per year, the total units of analysis are 2,154 firm-years. The results show a decline in the average audit duration time before and after the establishment of an audit committee, 50 days before and 46 days after. The factors found significantly relating to the amount of time of examining corporate financial reports include both the corporate attribute factors and the auditor controlled factors, specifically the number of affiliated companies, organization performance, type of audit opinion, number of year of audit client, the length of auditor s report and adjusting and reclassification entries. Before establishing an audit committee, the results show a significant relationship between company size and audit duration whereas no significant relationships are found between audit duration and organizational performance, the length of auditor’s report and adjusting and reclassification entries. However, after the audit committee establishment, type of auditor is found to have negative relationship with audit duration and no relationship is found with type of audit opinion. The results provide an empirical evidence that the establishment of an audit committee to be a part of good corporate governance, can help companies better disclose their financial reports in a more timely manner.